VD_FINDINFO Jug / 2011 / 169 vom 11. April 2011 - VD Tribunal cantonal (2011)
VIOLENCE CONTRE LES AUTORITÉS, OPPOSITION À UN ACTE DE L'AUTORITÉ, ERREUR SUR LES FAITSDROIT PÉNAL | 13 CP, 285 ch. 1 CP, 286 CP